2012
DOI: 10.1093/annhyg/mes073
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Biological Monitoring of Platinum-Containing Drugs in Two Hospital Pharmacies Using Positive Air Pressure Isolators

Abstract: Environmental and biological monitoring of platinum containing drugs was implemented in two French hospital pharmacies using positive air pressure isolators and having similar working procedures when preparing antineoplastic drugs. Wipe sampling of surfaces, gloves, and vials was performed in the preparation room and in storage areas. All employees involved in the preparation of antineoplastic drugs were tested for urinary platinum on Monday before work and Friday after shift. Only traces of platinum were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A low percentage of contaminated workers, less than 20%, were reported in Europe [ 16 , 17 , 18 , 19 , 20 , 21 ]. Some other studies reported higher proportions of contaminated HCWs, >50% [ 22 , 23 , 24 ]. The results of these different studies are highly variable, probably due to the differences in study protocols, the investigated substances, or the limits of quantification of analytical methods.…”
Section: Discussionmentioning
confidence: 99%
“…A low percentage of contaminated workers, less than 20%, were reported in Europe [ 16 , 17 , 18 , 19 , 20 , 21 ]. Some other studies reported higher proportions of contaminated HCWs, >50% [ 22 , 23 , 24 ]. The results of these different studies are highly variable, probably due to the differences in study protocols, the investigated substances, or the limits of quantification of analytical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 19 studies that also evaluated control (also called unexposed) subjects, seven studies reported samples above the level of detection for both exposed and control subjects (Ensslin et al 1994a;Fransman et al 2007b;Kopp et al 2013a;, which suggested that environmental contamination that may be the issue. For example, in a small study of pharmacy personnel, reported that the urine samples both exposed and unexposed pharmacy staff tested positive for cyclophosphamide on the day they received training on use of the urine sample kits in the oncology laboratory (i.e., the five unexposed pharmacy staff were exposed by entering the oncology pharmacy).…”
Section: Biomonitoringmentioning
confidence: 99%